On suction driven flow and heat transfer in a pipe filled with porous media - Makinde, Oluwole Daniel; Sibanda, Precious (Computer Assisted Methods in Engineering and Science, 1998)
The axisymmetric flow of a viscous fluid and heat transfer in a pipe filled with porous media driven by suction at the pipe wall is examined. For low suction R.eynolds number flow, asymptotic solutions are developed. Using MAPLE, the solution series is extended and a bifurcation study is performed , Our results show that a decrease in the permeability of porous media may reduce the magnitude of heat transfer across the wall. The absence of real solutions of the given type between two turning points is also noticed and this gap of no solution disappears as the permeability of the porous media decrease